Design and Implementation of a Web-Based E-Tourism Platform for Rural Religious Tourism: A Community-Based Case Study - Danang Satrio; Didha Putri Citradika; Titi Rahayu Prasetiani; Dani Alfin P (Research Synergy Foundation, 2026)
This study aims to develop and evaluate a web-based e-tourism platform to enhance the promotion and accessibility of rural religious tourism in Indonesia. The research focuses on the shrine of Nyai Siti Ambariyah in Bukur Village, Pekalongan Regency, a culturally significant yet underpromoted pilgrimage site. A research and D approach using a prototype model was employed. Data were collected through literature review, observation, interviews with local stakeholders, and document analysis. The prototype website bukurdesareligi dot com was designed and iteratively refined based on community feedback. Evaluation methods included usability testing, SEO performance analysis, and Google Analytics. Usability testing involved 30 participants consisting of local community members, visiting tourists, and site administrators. Results showed that over 85 percent of users could easily access key features, including historical content, event schedules, and visitor services. The platform integrates cultural and spiritual narratives with digital technology, functioning not only as an information tool but also as a cultural archive documenting rituals, oral histories, and promoting local small enterprises, UMKM. Its responsive design ensures cross-device accessibility, while SEO optimization enhances online visibility. Compared to prior studies with static systems, this platform offers a more interactive and holistic solution. The study concludes that web-based e-tourism effectively supports the digitalization of rural religious tourism by improving promotion, engagement, and heritage preservation. It contributes a replicable, community-driven model, although further multi-site and long-term evaluation is recommended to ensure scalability and sustainability.